2019
DOI: 10.1002/ppul.24251
|View full text |Cite
|
Sign up to set email alerts
|

Household incense burning and children's respiratory health: A cohort study in Hong Kong

Abstract: Background: Incense burning is an important source of indoor air pollution in many Asian regions. We investigated the associations between household incense burning and lung function, lung function growth and respiratory diseases and symptoms in primary school children in Hong Kong.Methods: A total of 4041 children (mean age: 9.1 years) were recruited from 27 primary schools in Hong Kong. Information on incense burning and medical history of respiratory diseases and symptoms was collected by questionnaire. Spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Our finding is unique in that aspect and suggested that exposed to incense smoke increased lung impairment (AOR: 1.72; 95% CI: 1.21–3.85). The association is consistent with previous studies 6,8 . In Taiwan, a study reported lower values of FVC and FEV1 among adolescents with daily exposure to incense burning in home 6 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our finding is unique in that aspect and suggested that exposed to incense smoke increased lung impairment (AOR: 1.72; 95% CI: 1.21–3.85). The association is consistent with previous studies 6,8 . In Taiwan, a study reported lower values of FVC and FEV1 among adolescents with daily exposure to incense burning in home 6 .…”
Section: Discussionsupporting
confidence: 91%
“…In Taiwan, a study reported lower values of FVC and FEV1 among adolescents with daily exposure to incense burning in home 6 . In Hong Kong, incense burning was found to be associated with reduced peak expiratory flow (PEF) among children 8 . There are several studies that found association between air pollution exposures and lung function impairments among adult population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One plausible explanation was that respiratory problems were more prevalent in boys than in girls at the baseline. 55 Consistently, previous cross-sectional population-based studies among children also indicated that incense burning was associated to the increased risk of various respiratory diseases and symptoms such as asthma, cough, and wheeze in an exposure-response manner. 56–58 On the other hand, the opposite finding, that is, there was no significant relationship between incense burning with prevalence of respiratory problems including chronic cough, chronic sputum, chronic bronchitis, runny nose, wheezing, asthma, allergic rhinitis or pneumonia was reported in a cross-sectional investigation among 346 primary school children in Hong Kong.…”
Section: Evidence-based Associations Between Incense Burning and Health Effectssupporting
confidence: 71%
“…The original Kotz model is largely driven by age (17), but in the EHS cohort, age did not predict COPD in men or women (Table S1). Ex-or current smoking did not predict COPD as strongly in the EHS cohort as in the original Kotz model, possibly due to the small number of cigarettes smoked per day in Hong Kong and the existence of other context-specific causes of COPD (Table 1), such as incense burning (64,65). As previously, low BMI, low socioeconomic position, and ever drinking all predicted COPD (8,32,(37)(38)(39)(40)(41)(42)(43)(44)66,67).…”
Section: Risk Predictorsmentioning
confidence: 65%